Stromal Vascular Fraction and its Role in the Management of Alopecia: A Review - Stefanis, Athanasios J; Groh, Tomas; Arenbergerova, Monika; Arenberger, Petr; Bauer, Peter O (The Journal of clinical and aesthetic dermatology, 2019)
Adipose cells organized in small clusters under the reticular dermis closely interact with hair follicular cells and regulate the hair cycle. Intradermal adipocyte progenitor cells are activated toward the end of the telogen phase to proliferate and differentiate into mature adipocytes. These cells, surrounding the hair follicles, secrete signaling molecules that control the progression of the hair cycle. Diseases associated with defects in adipocyte homeostasis, such as lipodystrophy and focal dermal hypoplasia, lead to alopecia. In this review, we discuss the potential influence of stromal vascular fraction from adipose tissue in the management of alopecia as well as its involvement in preclinical and clinical trials.
Keywords: stromal vascular fraction; adipose tissue; Adipose-derived stromal/stem cells; hair loss; alopecia